2003
DOI: 10.1007/s00299-002-0531-3
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens-mediated transformation of Festuca arundinacea (Schreb.) and Lolium multiflorum (Lam.)

Abstract: Agrobacterium tumefaciens strain LBA4404 carrying plasmid pTOK233 encoding the hygromycin resistance (hph) and beta-glucuronidase (uidA) genes has been used to transform two agronomic grass species: tall fescue (Festuca arundinacea) and Italian ryegrass (Lolium multiflorum). Embryogenic cell suspension colonies or young embryogenic calli were co-cultured with Agrobacterium in the presence of acetosyringone. Colonies were grown under hygromycin selection with cefotaxime and surviving colonies plated on embryoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 23 publications
(47 reference statements)
2
42
0
Order By: Relevance
“…Finally, regenerated putative transgenic shoots were separated and transferred onto rooting medium containing half strength MS medium supplemented with 30 g/L sucrose, 2 g/L Gelrite, 250 mg/L cefotaxime, and 50 mg/L hygromycin. While, in the earlier study (Bettany et al 2003), putative transgenic calli were selected with relatively higher concentration of hygromycin (75 mg/L), the present study we found that selection of putative transformant callus with higher than 50 mg/L hygromycin caused a severe inhibition of shoot regeneration from the Hm-resistant calli. In addition, it has been reported that continuous selection of low concentration of hygromycin produced higher number of transgenic plants without escape (Dalton et al 1995).…”
Section: Selection and Regeneration Of Transgenic Plantsmentioning
confidence: 51%
See 4 more Smart Citations
“…Finally, regenerated putative transgenic shoots were separated and transferred onto rooting medium containing half strength MS medium supplemented with 30 g/L sucrose, 2 g/L Gelrite, 250 mg/L cefotaxime, and 50 mg/L hygromycin. While, in the earlier study (Bettany et al 2003), putative transgenic calli were selected with relatively higher concentration of hygromycin (75 mg/L), the present study we found that selection of putative transformant callus with higher than 50 mg/L hygromycin caused a severe inhibition of shoot regeneration from the Hm-resistant calli. In addition, it has been reported that continuous selection of low concentration of hygromycin produced higher number of transgenic plants without escape (Dalton et al 1995).…”
Section: Selection and Regeneration Of Transgenic Plantsmentioning
confidence: 51%
“…It is also demonstrated that transgenic Italian ryegrass could be produced by the use of the easily available pCAMBIA1301 vectors. The transformation efficiency was comparable with other Agrobacteriummediated transformation systems in grass species such as, Italian ryegrass (Bettany et al 2003), perennial ryegrass (Wu et al 2005) and orchardgrass (Lee et al 2006). …”
Section: Molecular Analysis Of Transgenic Italian Ryegrass Plantsmentioning
confidence: 59%
See 3 more Smart Citations